The exercise of control in the diamond industry of South Africa: some preliminary remarks - Innes, Duncan (My University, 1975)
Though the diamond industry would, after a relatively short period of its life, be eclipsed by the gold industry in South Africa, the discovery of diamonds on a large scale ushered in a period of wealth and prosperity which altered the social history of the country in a dramatic way. Apart from the direct wealth produced by the industry (by 1936 over £320m worth of diamonds had been produced in South Africa) (1), the diamond mining industry encouraged the development of a large-scale infrastructural network both within the country and between South Africa and Europe.
African Studies Seminar series. Paper presented March, 1975
Keywords: Diamond mines and mining. South Africa